ŚIWATATTWA DALAM KONSTRUKSI KEAGAMAAN HINDU INDONESIA - I Gede Arya Juni Arta; I Komang Widyana (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The Balinese Hindu community who believes in Shiva Siddhanta places Shiva in a hierarchical order as the highest ruler of the universe and its contents, as sourced from the teachings of iwatattwa, such as: Bhuanakosa, Wrhaspati Tattwa, Ganapati Tattwa, Jnana Siddhanta and Jnana Tattwa. The understanding that Shiva being the highest ruler results in esoteric and exoteric implications. This research article examines the religious esotericism and exotericism of the Balinese Hindu community in the construction of the Siwatattwa teachings as well as the various uniqueness in implementing the Vedic teachings. This research employs literature studies and a qualitative design examining the study of arguments or narratives from texts or books containing Shivatattwa teachings. Based on the results of this study, it can be concluded that Shivatattwa teachings have imbued the religious construction of the Balinese Hindu community, which is implemented in Bhatara as a worship center, temples as places of worship, and tapak dara as a philosophy of life balance.key words: The Balines Hindu, Shiva, Siwatattwa